2016
DOI: 10.3846/16486897.2015.1127251
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perceptions of the Benefits and Barriers of Implementing Environmental Management Systems in the Nigerian Construction Industry

Abstract: Trinitrotoluene (TNT), a commonly used explosive for military and industrial applications, can cause serious environmental pollution. 28-day laboratory pot experiment was carried out applying bioaugmentation using laboratory selected bacterial strains as inoculum, biostimulation with molasses and cabbage leaf extract, and phytoremediation using rye and blue fenugreek to study the effect of these treatments on TNT removal and changes in soil microbial community responsible for contaminant degradation. Chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 28 publications
(34 reference statements)
0
59
0
2
Order By: Relevance
“…Demographical information was analysed by means of frequency analysis to provide a snapshot of the respondents' characteristics. As with many other environmental and construction studies that have used a weighted average method to analyse questionnaires data [54][55][56], a similar approach was adopted to analyse and rank the perceived benefits and barriers of Earthship building.…”
Section: Discussionmentioning
confidence: 99%
“…Demographical information was analysed by means of frequency analysis to provide a snapshot of the respondents' characteristics. As with many other environmental and construction studies that have used a weighted average method to analyse questionnaires data [54][55][56], a similar approach was adopted to analyse and rank the perceived benefits and barriers of Earthship building.…”
Section: Discussionmentioning
confidence: 99%
“…This is also corroborated by Olawumi et al (2016) that training and education are essential drivers for addressing skill shortfalls in the construction industry. In a study by Owolana and Booth (2016), it was revealed that such training that portrays lifelong learning practices is rare in the construction industry of many developing countries. Thus, the need for QS firms and other construction-related organisations to invest in training and education of staff becomes very important.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Gavronski et al 2013, Biondi et al (2000), Quazi et al (2001), Fryxell and Szeto (2002), Poksinska et al (2003), Yiridoe et al (2003), Jiang and Bansal (2003), Zutshi and Sohal (2004), González and González (2005), Schylander and Martinuzzi (2007), Arena 2012 Some specific issues to be remarked is that the specific environmental issues that have been reported as improvements were waste management (ZUTSHI; SOHAL, 2004;PSOMAS et al, 2011;DJEKIC et al, 2014;OWOLANA;BOOTH, 2016;TESTA et al, 2016;MELNYK, 2002;MELNYK, 2003), natural resources usage (SANTOS et al, 2016) and toxic releases (SZYMANSKI; TIWARI, 2004).…”
Section: Government Requirementmentioning
confidence: 99%